Konsep Akhlak pada Surah Al-A’raf ayat 199 (Studi Komparatif Tafsir Al-Munir dan Tafsir Ath-Thabari) - Safitri, Ummi Cahya; Romadlon, Arif Firdausi Nur; Ridho, Muhammad Mukharom (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study examines the meaning of ethics in Surah Al-A'raf, verse 199, using a comparative method between the Tafsir Al-Munir and Tafsir Ath-Thabari. Tafsir Ath-Thabari is one of the exegetes who lived during the classical era, while Tafsir Al-Munir is an exegete from the contemporary period. The purpose of this research is to understand the meaning of the concept of morality in Surah Al-A'raf verse 199 according to Al-Munir and Ath-Thabari, as well as to examine the comparison between the two interpreters regarding that verse. This research is based on a literature review that utilizes books available in libraries as well as digital resources that can be easily accessed. Based on the research findings, there are three fundamental morals contained in this verse, namely forgiving, doing good, and avoiding foolish people. The meaning of Al Afw is forgiveness, which is also referred to as noble character; the meaning of maruf is to do good and encourage others to do good, while turning away from foolish people is interpreted as protecting oneself from the negative influence of foolish individuals. Both interpretations have the same meaning, but there are differences in emphasis on several aspects.